Efficient and Practical Radiosynthesis of Novel [131I]-Xanthine and [131I]-Hypoxanthine - W. Nuraeni; E. Rosyidiah; H. Wongso (Atom Indonesia, 2022)
Natural products (NPs) have been the basis for the discovery and development of pharmacologically relevant drug-related molecules, including radiopharmaceuticals. Xanthine (3,7-dihydropurine-2,6-dione) and hypoxanthine (1,9-dihydro-6H-purin-6-one) are purine-based natural heterocyclic alkaloids that are generally found in some plants, animals, and the human body (e.g., muscle tissue, blood, and urine). The purpose of this study was to label xanthine and hypoxanthine with radioactive iodine-131 (a theranostic radionuclide) by a direct labeling method using chloramine-T as an oxidizing agent. Several experiments were performed to optimize the labeling efficiency by changing reaction conditions, including the ratio of starting material and chloramine-T, pH, solvent, temperature, and reaction time. Overall, labeling at acidic conditions in dimethyl sulfoxide (DMSO) resulted in considerable low radiochemical yields (RCYs) (< 4.0 %), and therefore the focus was shifted to exploit the alkaline reaction conditions. The optimized reaction condition: pH (10.5-11.0), xanthine:chloramine-T ratio (1:2), reaction temperature (27 ºC), and reaction time (30 min),  provided [131I]-xanthine with a RCY of 65.8 ± 0.1 %. After purification with extraction using chloroform (CHCl2), the radiochemical purity (RCP) of 95.1 % was achieved, as indicated by radio-thin layer chromatography (radio-TLC) analysis. In addition, the labeling of hypoxanthine was accomplished in a maximum 60.3 ± 0.2 % RCY, and after purification a RCP of 94.2 % was obtained. The present results provide an efficient and practical labeling method for xanthine and hypoxanthine with iodine-131, suggesting that these radiolabeled compounds can be further investigated in in vitro and in vivo studies for their theranostics potential.